(untitled) (BioLaw Journal - Rivista di BioDiritto, 2026)
The article examines the emblematic case of the Istanbul Convention – a Council of Europe treaty aimed at preventing and combating violence against women – which in all Central and Eastern European (CEE) countries has been the subject of deliberate distortion campaigns carried out by illiberal and populist actors. These actors have presented it as part of an alleged project by Western European elites to enforce “gender ideology”, promote LGBTQ+ rights, and undermine state sovereignty. This narrative, constructed through the strategic use of moral, cultural, and legal categories, has transformed an instrument designed to protect human rights into a symbol of “Western interference”, thereby contributing to the delegitimization of both international cooperation on gender equality and the authority of European institutions themselves.